Plant calcium dynamics: signalling the way to sustainable food production - Mills, Hayley (2021)
In this work we explore the calcium signalling pathway mediating symbiotic associations between legumes and Nitrogen-fixing bacteria. This symbiotic process has been identified as a possible 'biological' alternative to using environmentally damaging synthetic fertilisers in crop production. Therefore, motivated by the challenge of ensuring worldwide food security whilst utilising increasingly degraded soils, we look to advance the knowledge of the signalling pathway that facilitates nodulation in order to progress towards the transfer of this favourable trait from legumes to cereal crops.